Optimization of enzymatic hydrolysis process of distiller's grains based on response surface method - PANG Qiong, XUE Shasha, LI Zhuoyuan, ZHAO Jia, HAO Jianwei, SHI Shengli, LIU Xiaoxia, LUO Aiguo (Zhongguo niangzao, 2024)
In order to improve the enzymatic hydrolysis efficiency of distiller's grains and promote the resource utilization of distiller's grains, using distiller's grains as the raw material and the yield of reducing sugar as the evaluation index, combined with the single factor test results, the significant factors were screened by Plackett-Burman tests, and the enzymatic hydrolysis process conditions of distiller's grains were optimized by response surface method. The microstructure of raw material, Fenton reagent pretreated and enzymatic hydrolyzed distiller's grains were observed by scanning electron microscope (SEM). The results showed that the optimum enzymatic conditions were as follows: treatment time 27 h, pH 4.7, cellulase addition 1 060 U/g, enzymatic hydrolysis pH 4.9. Under the optimized conditions, the yield of reducing sugar was 64.44%, which was 148.37% higher than that of the control group. SEM results showed that after Fenton reagent pretreatment and enzymolysis, the surface morphology of distiller's grains was bulky, the structure of wood fiber was destroyed, and the porosity increased. After further enzymatic hydrolysis, the bulk material was significantly reduced and many small holes were exposed, which indicated that the yield of reducing sugar was directly related to the change of surface morphology.